Belgické německojazyčné společenství a další německojazyčné skupiny v Belgii - Petr Kokaisl; Pavla Kokaislová (AntropoWebzin)
The main aim of this paper is to show the specificity of the perception of own ethnicity of the German-speaking population living in the German-speaking Community in Belgium. Seeing that the German-population (or population speaking German dialect) live outside the autonomous region too, it is possible to make relatively efficient compared to the influence of government in shaping ethnicity and language. The territory of the German-speaking Community has today some 74 500 inhabitants. To the north is the densely populated Eupen county, to the South lies the rural, tourism-oriented Belgian Eifel. The territory comprises a total of 854 km2. The German-speaking Community is one of the smallest self-governed entities in Europe and has a large autonomy – the official, school and court language is German. This paper should give an answer to the question: What shapes the ethnicity of the German-speaking population? (Language, location, historical traditions, the common historical origin...) and What effect has the official status of the language used in its development and use?